Protecting Computer Systems from Cyber Attacks with Internal Interface Diversification - Sampsa Rauti (My University, 2022)
Internal interface diversification is a proactive technique that protects software and devices from malicious cyber attacks by making interfaces unique in every separate system. As malware cannot use the knowledge about internal interfaces in the system to its advantage anymore, it is rendered useless. The current study gauges the effectiveness of internal interface diversification by analyzing three cyber attacks as case studies and showing why internal interface diversification is an effective countermeasure against them. The study will further serve to demonstrate that internal interface diversification is a feasible and widely applicable security measure against numerous common cyber attacks.
Security in Computing and Communications: 7th International Symposium, SSCC 2019, Trivandrum, India, December 18–21, 2019, Revised Selected Papers